2021
DOI: 10.1001/jamanetworkopen.2021.5344
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Health Care Worker Intentions to Receive a COVID-19 Vaccine and Reasons for Hesitancy

Abstract: Although health care workers (HCWs) can serve as ambassadors of COVID-19 vaccine acceptance, surveys have found low acceptance rates among HCWs (eg, 33.5%). 1 However, those surveys were conducted before the issuance of vaccine emergency use authorizations (EUAs) by the US Food and Drug Administration (FDA). We surveyed all employees of a health care system on the eve of vaccine distribution to encourage them to receive a COVID-19 vaccine, assess their intentions to do so, and understand reasons for hesitancy.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 6 publications
(13 reference statements)
4
82
1
1
Order By: Relevance
“…Availability of vaccines was a significant promoter for COVID-19 vaccines acceptance among dental students globally, as the students who believed that COVID-19 vaccines would be available for them were less hesitant (28.1% vs. 14.4%; p < 0.01). In the USA, COVID-19 vaccine acceptance levels increased gradually over the last months, which indicates that increasing trends of vaccine acceptance may correlate positively with the shift from hypothetical vaccines to the availability of real-world vaccines with substantial effectiveness and safety [74]. In the UMHI group, Italy was the most accepting country (4.7 ± 0.8), while Russia was the least accepting country (2.85 ± 1.12).…”
Section: Discussionmentioning
confidence: 96%
“…Availability of vaccines was a significant promoter for COVID-19 vaccines acceptance among dental students globally, as the students who believed that COVID-19 vaccines would be available for them were less hesitant (28.1% vs. 14.4%; p < 0.01). In the USA, COVID-19 vaccine acceptance levels increased gradually over the last months, which indicates that increasing trends of vaccine acceptance may correlate positively with the shift from hypothetical vaccines to the availability of real-world vaccines with substantial effectiveness and safety [74]. In the UMHI group, Italy was the most accepting country (4.7 ± 0.8), while Russia was the least accepting country (2.85 ± 1.12).…”
Section: Discussionmentioning
confidence: 96%
“…The concerns cited by the respondents with regard to the COVID-19 vaccines were largely shared with participants in other studies [16][17][18]24]. To counteract these concerns, it may be helpful to highlight what is known so far about the adverse effects of COVID-19, so that people can weigh the risks and benefits of vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research extended the PMT by including knowledge [28] and revealed that high knowledge about vaccine designs and protection mechanisms may increase an individual's motivation to receive a vaccination [29]. Several studies have examined the predictors of HCW motivation to receive COVID-19 vaccination and revealed that low perceived risk of contracting COVID-19 [30], low trust in vaccine effectiveness [31,32], high concerns about unknown risks of the COVID-19 vaccines [31,[33][34][35], and high concerns about time spent on vaccination [32] were associated with hesitancy to receive COVID-19 vaccination. Although the factors examined in these studies are included in the threat and coping appraisals of PMT, no study has examined the comprehensive PMT constructs that relate to frontline HCW motivation to receive COVID-19 vaccination.…”
Section: Protection Motivation Theorymentioning
confidence: 99%
“…The results indicated that programs promoting COVID-19 vaccination for the public should mitigate uneasiness by providing clear information about the vaccination using language accessible to a general audience. Studies have revealed that high concern about the unknown risks of COVID-19 vaccines [31,[33][34][35] and about time spent on vaccination [32] were primary reasons for vaccination hesitancy in HCWs and other employees in the health care system. However, the present study did not reveal the same result for frontline HCWs.…”
Section: Pmt Factors Related To Motivation To Receive Covid-19 Vaccination In Frontline Hcws and In The Publicmentioning
confidence: 99%